Carers' perception of childhood asthma and its management in a selected Pakistani community. Issue 4 (1st October 2002) - Hazir, T; Das, C; Piracha, F; Waheed, B; Azam, M
Abstract : Aims: To gather information on the level of disease awareness among the carers of asthmatic children and to determine whether it can help us draw inferences about the possible impact of prevailing perceptions on the management of asthma? Methods: Subjects were children's parents/guardians visiting the asthma clinic, Children's Hospital, Islamabad. The questionnaire included items on general understanding of asthma, its triggers, and management. Results: Two hundred carers of asthmatic patients participated. Thirty six per cent thought that asthma is a communicable disease. Rice and oily foods were blamed for asthmatic exacerbations in up to 57% of cases; 82% felt that inhalation therapy is effective in controlling asthma symptoms. Conclusions: Asthma awareness is inadequate. The majority of the carers unnecessarily blamed and withheld many nutritious foods. Social stigmata can undermine the self esteem of growing asthmatics. Lack of awareness is not significantly related to the socioeconomic or educational background. Awareness raising strategies are needed in the community.